Determination of phthalic acid esters and di(2-ethylhexyl) adipate in fish and squid using the ammonium formate version of the QuEChERS method combined with gas chromatography mass spectrometry. (30th June 2022) - Sambolino, Annalisa; Ortega-Zamora, Cecilia; González-Sálamo, Javier; Dinis, Ana; Cordeiro, Nereida; Canning-Clode, João; Hernández-Borges, Javier
Graphical abstract: Highlights: A group of plasticizers has been determined in fish and squid by QuEChERS-GC–MS. Ammonium formate version of the QuEChERS method was first applied to such samples. Negligible matrix effect was observed for most analytes and matrices. Thirty samples of Scomber colias, Loligo gahi and Katsuwonus pelamis were analysed. DIBP, DBP and DEHP were quantified in some of the samples. Abstract: In the present study, the ammonium formate version of the QuEChERS method, considered highly advantageous in relation to instrument maintenance and other issues, was applied for the first time to extract a group of twelve phthalic acid esters (PAEs, i.e. dipropyl phthalate, DPP; diisobutyl phthalate, DIBP; dibutyl phthalate, DBP; diisopentyl phthalate, DIPP; di- n -pentyl phthalate, DNPP; dihexyl phthalate, DHP; butyl benzyl phthalate, BBP; dicyclohexyl phthalate, DCHP; di(2-ethylhexyl) phthalate, DEHP; di- n -octyl phthalate, DNOP; diisononyl phthalate, DINP; and diisodecyl phthalate, DIDP) and one adipate (di(2-ethylhexyl) adipate, DEHA) from two species of fish ( Scomber colias and Katsuwonus pelamis ) and one of squid ( Loligo gahi ). The method was validated in terms of linearity, trueness and matrix effects. Determination coefficients (R 2 ) for matrix-matched calibration curves were higher than 0.99 in all cases, being the lowest calibration levels in the range 0.5–10 ng/g. Mean recovery values were between 70 and 117% with relative standard deviation values ≤20%. Matrix effects were soft (between −20 and +20%) for most analytes and matrices, except in squid samples, which was mostly medium with a moderate ion suppression. The analysis of 10 samples of each type showed the presence of DIBP, DBP and DEHP at concentrations up to 44.2 ± 2.1 ng/g of wet weight in some of the samples and species, still not representing concerning values when considering the daily intake of such species of seafood in the human diet (tolerable daily intake -TDI- values were not exceeded). Results demonstrated that the ammonium formate version of the QuEChERS method can be applied with success for the extraction and determination of the selected PAEs and DEHA in fish and squid samples.